1989
DOI: 10.1111/j.1365-2125.1989.tb03434.x
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of prescription information leaflets (1).

Abstract: 1 Prescription information leaflets (PILs) giving information about non-steroidal antiinflammatory drugs (NSAIDs), ,B-adrenoceptor antagonists and inhaled bronchodilators were evaluated in three small Hampshire towns, while a fourth, in which no leaflets were distributed, acted as a control. 2 Seven hundred and nineteen (82%) patients prescribed one of these medicines agreed to be interviewed in their homes, 1 to 2 weeks after the medicine had been prescribed. Four hundred and nineteen of them had received lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
3
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(80 citation statements)
references
References 34 publications
(38 reference statements)
2
74
3
1
Order By: Relevance
“…82 No trials reported an adequate means of concealing the randomisation process from the treatment provider, while four reported using an inadequate method. 34,79,84,86 Adequate blinding of the outcome assessor was reported in six trials. 34,78,80,81,84,86 Loss to follow-up, reported in eight trials, averaged 21%.…”
Section: Description Of Included Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…82 No trials reported an adequate means of concealing the randomisation process from the treatment provider, while four reported using an inadequate method. 34,79,84,86 Adequate blinding of the outcome assessor was reported in six trials. 34,78,80,81,84,86 Loss to follow-up, reported in eight trials, averaged 21%.…”
Section: Description Of Included Trialsmentioning
confidence: 99%
“…34,78,85,97,99 The source of funding was reported in 16 trials. 79,81,[83][84][85]87,88,[95][96][97]99,100,103,104,106,107 Eleven trials were funded by a national funding body, four were funded by a charitable organisation and two were funded by a pharmaceutical company. One trial received joint funding from both a research council and pharmaceutical company.…”
Section: Effectiveness Review Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study corroborates the disparities between the results of the tests of readability of the written materials and the results of health literacy of potential users of those leafl ets. 9 Although almost all of the recent studies are focused on the description of information gaps on the PL or in its low impact on changing the behavior of its users, 2 there seems to be no effective substitute for these pieces of written information, mandatory for drugs marketed in Europe. Thus, it would be appropriate to develop procedures for assessing readability that controlled the effect of variations in health literacy simultaneously, also performing an assessment of the acquisition of the knowledge acquired by reading the PL.…”
Section: Discussionmentioning
confidence: 99%
“…4 One of the most important written materials that users receive about the use of drugs is the respective package leafl et (PL). 2 All medicinal products placed on the Community market in the European Union are required to be accompanied by labeling and package leafl et, which must provide a set of comprehensible information enabling the use of the medicinal product safely and appropriately, complementing the information provided by health professionals. Although it…”
Section: Introductionmentioning
confidence: 99%